Procedure for the deepening of depression in an 8-year-old child with intellectual distability in an integrated school - Atrashkevich, Yuliya; Pawełko, Agnieszka; Ciechacka, Maria (Journal of Education, Health and Sport, 2025)
Depression is a health problem that is increasingly diagnosed in children and adolescents. The presentad worki s a case study of a child with intellectual disabilities. In the first part, depressive states in children with intellectual disabilities were described. The second part presentes care procedur es in the event of deepening depression in an 8 –year-old child with intellectual distability in an integrated school. Thea im of the work is to plan nursing care for a child with depression in an integrated environment. The care process included the child’s mental,physical and sexual problems, golas and patient care plan in an integrated school.